Validity of Automatic Approval in Smart Contracts as a Form of Agreement under Indonesian Civil Law - Muchamad Yusva Mufazis; Tahasak Sahay; Andika Wijaya (Manunggal Halim Jaya, 2026)
The development of digital technology, especially blockchain, has given birth to a new innovation in the world of contract law known as smart contracts. These contracts work automatically through programming code, so their execution no longer relies on human intervention. This provides various advantages such as a faster, more transparent process, and minimal risk of breach of agreement. However, the emergence of smart contracts also raises an important question: whether this form of agreement is in accordance with the applicable legal provisions in Indonesia, especially regarding the requirements for the validity of agreements and the recognition of electronic agreements. This study shows that basically smart contracts can be considered valid as long as the parties really understand and agree on the mechanisms embedded in the system. This means that even if the agreement is done digitally and automatically, the important elements of the agreement can still be met. On the other hand, there are still several challenges that need to be considered, such as difficulties in proving in the event of a dispute, limitations in making contract changes, and the possibility of inequality in technology understanding between parties. Compared to countries such as the United States, which are already more adaptive, Indonesia still needs more specific arrangements so that the use of smart contracts can provide legal certainty as well as adequate protection for the parties.